2006
DOI: 10.1038/sj.npp.1301175
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low Doses of Δ-9 Tetrahydrocannabinol on Reinforcement Processing in the Risky Decision-Making of Young Healthy Adults

Abstract: Research suggests that risky decision-making is sensitive to neuromodulatory influences acting upon corticolimbic circuitry. However, while other evidence attests to effects of D-9 tetrahydrocannabinol (THC) on the activity of reward pathways, relatively little is known about the possible involvement of cannabinoid activity in risky choice. In this experiment, we examined the effects of a single sublingual 5 mg dose of THC on a test of risky decision-making (requiring choices between simultaneously presented g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
2
11
1
1
Order By: Relevance
“…This contrasts recent PET data showing that in 1-day abstinent heavy marijuana smokers regional blood flow in the ventromedial prefrontal cortex and cerebellum was increased during performance in the Iowa gambling task [114]. In keeping with the aforementioned behavioral findings of altered cost-benefit processing induced by THC [106] or in heavy marijuana users [111], fMRI approaches indicate accompanying reductions in brain activation in regions such as the anterior cingulate cortex, medial frontal cortex and cerebellum, particularly during loss of reward [115,116]. Notably, despite the high densities of cannabinoid CB1 receptors in basal ganglia structures in the human brain [19], their involvement and possible differential activation by exogenous cannabinoids in risky decision making is not as pronounced as that of prefrontal cortical regions from the current neuroimaging work.…”
Section: Empirical Evidence For Cannabinoid Receptor Modulation Of Vacontrasting
confidence: 81%
See 2 more Smart Citations
“…This contrasts recent PET data showing that in 1-day abstinent heavy marijuana smokers regional blood flow in the ventromedial prefrontal cortex and cerebellum was increased during performance in the Iowa gambling task [114]. In keeping with the aforementioned behavioral findings of altered cost-benefit processing induced by THC [106] or in heavy marijuana users [111], fMRI approaches indicate accompanying reductions in brain activation in regions such as the anterior cingulate cortex, medial frontal cortex and cerebellum, particularly during loss of reward [115,116]. Notably, despite the high densities of cannabinoid CB1 receptors in basal ganglia structures in the human brain [19], their involvement and possible differential activation by exogenous cannabinoids in risky decision making is not as pronounced as that of prefrontal cortical regions from the current neuroimaging work.…”
Section: Empirical Evidence For Cannabinoid Receptor Modulation Of Vacontrasting
confidence: 81%
“…Thus, under conditions with uncertainty about the likelihood of punishment, activation of cannabinoid CB1 receptors influences the sensitivity to reinforcement as well as punishment. These findings have been further substantiated by several recent studies implementing neurocognitive risk-based decision making tasks such as the Iowa Gambling Task and related gambling tasks in healthy volunteers and marijuana users [106,107]. Briefly, in the Iowa Gambling Task originally developed by Bechara and coworkers [108] subjects have to make a cost-benefit assessment based on their decisions and are able to draw cards from one of four decks to obtain monetary reward.…”
Section: Empirical Evidence For Cannabinoid Receptor Modulation Of Vamentioning
confidence: 86%
See 1 more Smart Citation
“…Embora a literatura esteja repleta de estudos sobre o efeito do uso de cannabis na atenção, memória operacional e funções executivas (Chang et al, 2006;Jager et al, 2006;Kanayama et al, 2004, Solowij et al, 2002, aprendizagem associativa (Nestor et al, 2008) e decisão (Rogers et al, 2007;Whitlow et al, 2004), ainda há poucos estudos sobre o efeito dessa substância na percepção emocional, especificamente, e emoção como um todo.…”
Section: Percepção Emocional Em Usuários De Cannabisunclassified
“…We also do not know whether, or how, regular users may develop compensatory strategies during acute intoxication to facilitate performance that might otherwise be impaired. For example, in a risky decision-making task, Rogers et al (2007) showed a reduction of risky behavior following lowdose sublingual administration of THC to healthy young adults (not regular cannabis users), with an adoption of more cautious cognitive strategies to compensate for the perceived disruption of effective decision making by cannabis. Thus regular users, due to their greater experience with cannabis, might be more likely to develop alternate compensatory strategies.…”
Section: Short-term Effects In Humansmentioning
confidence: 99%